DEVELOPMENT OF MUSIC-BASED LEARNING MODELS TO INTRODUCE LETTERS AND NUMBERS OF EARLY CHILDHOOD - Risdianto Hermawan (UPI Kampus Cibiru, 2021)
Basically, early childhood has extraordinary abilities, especially in the process of development. Therefore, it is necessary to optimize child development appropriately, and avoid burdening or forcing children. One of the strategies in developing early childhood education is through a music-based learning model.This study aims to describe and analyze how the development of a music-based learning model to introduce letters and numbers in early childhood. This papper is methodologically close to development research or what is commonly called Research and Development.The results of the development of a music-based learning model to introduce letters and numbers in early childhood are a form that is implemented to develop students' knowledge and abilities in recognizing letters and numbers. This research also produces a product in the form of music that can be applied to provide material for introducing letters and numbers to children. Students tend to be more able to understand or recognize letters and numbers using music so that children's abilities and understanding develop more optimal.